-6x+7=5x-3

Simple and best practice solution for -6x+7=5x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+7=5x-3 equation:


Simplifying
-6x + 7 = 5x + -3

Reorder the terms:
7 + -6x = 5x + -3

Reorder the terms:
7 + -6x = -3 + 5x

Solving
7 + -6x = -3 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
7 + -6x + -5x = -3 + 5x + -5x

Combine like terms: -6x + -5x = -11x
7 + -11x = -3 + 5x + -5x

Combine like terms: 5x + -5x = 0
7 + -11x = -3 + 0
7 + -11x = -3

Add '-7' to each side of the equation.
7 + -7 + -11x = -3 + -7

Combine like terms: 7 + -7 = 0
0 + -11x = -3 + -7
-11x = -3 + -7

Combine like terms: -3 + -7 = -10
-11x = -10

Divide each side by '-11'.
x = 0.9090909091

Simplifying
x = 0.9090909091

See similar equations:

| 7x+4=2(x-7) | | 2x+3x+1=1+5x | | -10(-38u+44)=-40(-3u+37) | | g^2-19g+60=0 | | 18-3(x+5)=-21 | | 3x-1=-1+3 | | 38+15=180 | | (3*3)+y=3y | | 10+z/3= | | 5(-5x)5-7x=5 | | 1.5(x+4)-x=9 | | 10/-3= | | 5x+9+3x=65 | | B^2+b-20=0 | | 4=2(6p-10) | | 4x-1=1+4x | | -6(x-2)=30 | | p+(0.5p+3)=21 | | (3*3)+y=xy | | 3y^9-3y^5= | | 20x+2=142 | | -9x+12=48 | | .75(8x-4)+3=.4(5x+10)-1 | | 20x+2=38 | | 2x+1=5+2x | | 6x=(4x+16) | | 5x+3+8x-5=180 | | 4(2y+3+6y)=32y+12 | | 6-3x=3(8-x) | | b^2+24=-11b | | 3x+y=xy | | p^2+2p=35 |

Equations solver categories